Quality Assurance in Southeast Asia’s Higher Education: some lessons for Africa? - (:unkn) unknown (My University, 2024)
Most countries have quality assurance (QA) systems to monitor and improve their educational policies. Typically, such systems aim at enhancing transparency, assessing performance, and providing appropriate guidelines for forward-looking practices. Higher education institutions (HEIs) in developed countries have implemented QA systems that ensure consistent and transparent achievements. The main objective herein is to evaluate existing practices, identify crucial strategies for future planning as well as draw lessons that can be applied to Sub-Saharan African countries. Nevertheless, the review has indicated that though both areas have embraced Western-influenced QA frameworks, Southeast Asian nations are more successful in domesticating these systems. Fundamentally, it emphasizes that global standards must be reconciled with context-specific approaches and suggests how effective quality assurance systems can be developed in Sub-Saharan Africa.
Keywords: African Research